Effectiveness of ASN Recruitment Using the CAT System in Deli Serdang Regency, North Sumatra Province - Rahman, Faisal; Adam, Adam; Lubis, Maksum Syahri (Universitas Medan Area, 2025)
This study analyzes the effectiveness of State Civil Apparatus (ASN) recruitment through the Computer Assisted Test (CAT) system in Deli Serdang Regency, North Sumatra Province. A qualitative descriptive research method was used with an inductive approach to systematically describe the phenomena in the field. The results of the study indicate that the implementation of the CAT system increases time efficiency, transparency, and selection accuracy. This system allows test results to be displayed directly and facilitates electronic data management. However, several challenges remain, including limited technological infrastructure, low technological literacy of participants, and less than optimal coordination between teams. These obstacles affect the smooth implementation of the selection, especially in remote areas. Recommendations for improvement include improving infrastructure, technology training, and strengthening coordination between teams. With these steps, the CAT system has the potential to become a more modern and efficient ASN selection model.